ANALISIS KEMAMPUAN PEMAHAMAN SISWA MELALUI MODEL PEMBELAJARAN PAI: DENGAN MENGGUNAKAN SPSS 26 - Euis Rosita; Hasan Basri; Yani Suryani; Agus Salim Mansyur (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2020)
As an Islamic education system, it contains various components that are interrelated. However, it is often done as is, without careful planning and concepts. So that the quality of Islamic education is not running as expected. In essence, the arrangement of learning models in education is intended to ensure that every educator has the ability to provide optimal service so that every educator must have a reference model of learning that is in accordance with the learning material. This study aims to determine the ability of students to understand the Akidah Akhlaq subject, through 3 groups of different learning models (Independent Samples). This is important to discuss so that teachers can ensure the achievement of learning objectivity through the application of various learning models.This research method uses a quantitative descriptive approach. Participants in this study were 25 students of class 3A and 25 students of class 3B of MI Tarbiyatul Ula and 30 students of grade 3 of MI Al-Muawanah. The instrument that uses daily test results from three different learning models, namely Group to Group Exchange (GGE), Group Investigation (GI), and Conventional (Lecture), is then analyzed using the SPSS Version 26 application.The results showed that there was no difference in the student's understanding ability (KPS) in the Akidah Akhlaq subject, between students who studied with GGE and students who studied with GI. There is a difference between students who study with GGE and students who study with conventional. There is a difference between students who study with GI and students who learn with conventional. This shows that the GGE learning model has good effectiveness in increasing students' understanding ability.